O cumprimento do orçamento como indicador de alcance da estratégia - Rana, Gabriela Maria Pol (2010)
This paper aims to seek to list the possible limitations related to the Budget Business as its suitability for Strategic Planning. The development of this work was based on a theoretical conceptualization of a model of organizational management, and empirical research in the form of a questionnaire for managers of the financial responsibility for budget preparation. The survey sample consists of 20 companies responding to this questionnaire in the universe of 270 companies formed by the 10 largest companies in 27 sectors listed in the journal Valor 1000 of August 2007. At the end of the analysis of questionnaire responses and comparisons with the theoretical conceptualization of the issue came to the conclusion that 55% of the companies prepare the budget based on strategic planning, however, who do not are failing at the stage of control and planning phases. In the control phase the fault is in the system of performance measurement, which is not consistent with the strategic goals, not favoring the alignment of the budget process to strategy. In the planning phase, the result of research showed us that there is also failure to communicate the strategy for those involved in budgeting. The length of time high in drawing up the budget process is also a limitation of the alignment of the budget to corporate strategy